2022
DOI: 10.3390/nu15010097
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Chronic Kidney Disease (CKD): A Practical Approach

Abstract: Chronic kidney disease has become a serious public health issue, as well as others health problems such as hypertension, DM, and obesity. Mediterranean diet (MD) can reduce the risk of cardiovascular disease and cancer and can lead to weight loss in obesity. There are studies that suggest that MD could be the diet of choice for patients with CKD for its influence on endothelial function, inflammation, lipid profile and blood pressure. There are few studies that tell us how to adapt MD to this group of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Weight loss and RAAS blockers have a protective effect on obesityrelated CKD (21). Mediterranean diet (MD) can lead to weight loss in obesity and may preserve renal function and delay CKD progression in overweight/obese adults for its in uence on endothelial function, in ammation, lipid pro le and blood pressure (22,23). However, weight loss and homeostatic disturbances of both energy and protein balances are characteristics of several illnesses including cancer, heart failure, and CKD (24).…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss and RAAS blockers have a protective effect on obesityrelated CKD (21). Mediterranean diet (MD) can lead to weight loss in obesity and may preserve renal function and delay CKD progression in overweight/obese adults for its in uence on endothelial function, in ammation, lipid pro le and blood pressure (22,23). However, weight loss and homeostatic disturbances of both energy and protein balances are characteristics of several illnesses including cancer, heart failure, and CKD (24).…”
Section: Discussionmentioning
confidence: 99%
“…The main recommendations of the Mediterranean diet in part meet the needs of the subject with CKD, such as a reduction in meat consumption, contributing to reduced animal protein intake; the use of plant-based foods, increasing consumption of plant-based proteins; the presence of high amount of fibers, vitamins, alkali and polyphenols, contributing to gut microbiota homeostasis and preventing inflammation; the use of extra virgin olive oil, rich in energy deriving from fats of vegetable origin and rich in polyphenols [23,24]. Some concerns remain on the potential risk of hyperkalemia linked to the high prevalence of plantbased foods.…”
Section: Mediterranean Diet and Kidney Diseasementioning
confidence: 99%
“…Poultry, red meat and eggs are limited but not entirely excluded. It has many physiological benefits, including improve blood pressure control, lipid profile, reduce systemic inflammation and maintain body weight [56]. A recent review summarized all cohort studies and observed a benefit in lowering the risk of albuminuria, incident chronic kidney disease or slowing the progression of chronic kidney disease with better adherence to Med diet.…”
Section: Healthy Dietary Patternmentioning
confidence: 99%